FINANCIAL TRANSPARENCY ON THE WEBSITE IN ASIAN BANKING INDUSTRY - Ana Dwi Pertiwi; Budi Hermana (Jurnal Ilmiah Ekonomi Bisnis, 2017)
New regulation of Bank Indonesia is required Indonesian banking to have a website to publish financial report though their website in order to improve transparency. Internet is considered as one of media which have a close relationship with transparency. This study was conducted to know financial transparency on the website in Asian banking industry. In this study, financial transparency on the website was measured by using internet financial reporting index. This study also evaluates the relationship performance, internet financial reporting index, information richness and website popularity. Sampling technique used in this study was purposive sampling. The samples in this study were 144 banks in Asia. And, an analytical technique in this study was Structure Equation Model (SEM) based components or Partial Least Square (PLS) with the help of Smartpls 2.The results of this study show that all of Asian banking in this study was implemented internet financial reporting. The results of this study also show that performance has a significant relationship to website popularity indirectly through information richness, the performance hasn’t a significant relationship to website popularity indirectly through internet financial reporting but internet financial reporting is influenced by performance, and the performance hasn’t a significant relation directly to website popularity. Keywords: banking; financial disclosure; internet financial reporting index